Risk factors for hepatic steatosis in adults with cystic fibrosis: Similarities to non-alcoholic fatty liver disease - Fares Ayoub; Cesar Trillo‐Alvarez; Giuseppe Morelli; Jorge Lascano (2018)
To investigate the clinical, biochemical and imaging characteristics of adult cystic fibrosis (CF) patients with hepatic steatosis as compared to normal CF controls.We performed a retrospective review of adult CF patients in an academic outpatient setting during 2016. Baseline characteristics, genetic mutation analysis as well as laboratory values were collected. Abdominal imaging (ultrasound, computed tomography, magnetic resonance) was used to determine presence of hepatic steatosis. We compare patients with hepatic steatosis to normal controls.Data was collected on 114 patients meeting inclusion criteria. Seventeen patients (14.9%) were found to have hepatic steatosis on imaging. Being overweight (BMI > 25) (P = 0.019) and having a higher ppFEV1 (75 vs 53, P = 0.037) were significantly associated with hepatic steatosis. Patients with hepatic steatosis had a significantly higher median alanine aminotransferase level (27 vs 19, P = 0.048). None of the hepatic steatosis patients had frank CF liver disease, cirrhosis or portal hypertension. We found no significant association with pancreatic insufficiency or CF related diabetes.Hepatic steatosis appears to be a clinically and phenotypically distinct entity from CF liver disease. The lack of association with malnourishment and the significant association with higher BMI and higher ppFEV1 demonstrate similarities with non-alcoholic fatty liver disease. Long term prospective studies are needed to ascertain whether CF hepatic steatosis progresses to fibrosis and cirrhosis.